1987
DOI: 10.1177/00220345870660061101
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent Cells in the Normal Dental Pulp

Abstract: The existence and location of various immunocompetent cells in the human dental pulp were investigated. Pulp tissue for analysis was obtained both from clinically intact pre-molars and from third molars without restorations or caries. Frozen and acetone-fixed pulp tissue sections were subjected to indirect immunohistochemistry with monoclonal antibodies to the following cell types: all peripheral T cells, helper/inducer T cells, cytotoxic/suppressor T cells, macrophages, B cells, and Class II antigen-expressin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
79
0
22

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 16 publications
3
79
0
22
Order By: Relevance
“…The abundance of class II MHC antigen-expressing cells in the normal dental pulp (JONTELL et al, 1987(JONTELL et al, , 1988OKIJI et al, 1992;OHSHIMA et al, 1994OHSHIMA et al, , 1996OHSHIMA et al, , 1997YOSHIBA et al, 1996) implies important roles played by these cells in maintaining physiological conditions of the pulp tissue. Of particular interest is the location of these cells.…”
Section: This Immunocytochemicalmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of class II MHC antigen-expressing cells in the normal dental pulp (JONTELL et al, 1987(JONTELL et al, , 1988OKIJI et al, 1992;OHSHIMA et al, 1994OHSHIMA et al, , 1996OHSHIMA et al, , 1997YOSHIBA et al, 1996) implies important roles played by these cells in maintaining physiological conditions of the pulp tissue. Of particular interest is the location of these cells.…”
Section: This Immunocytochemicalmentioning
confidence: 99%
“…Recent immunohistochemical studies have revealed the presence of class II major histocompatibility complex (MHC) antigen-expressing cells in the dental pulp (JONTELL et al, 1987(JONTELL et al, , 1988OKIJI et al, 1992;OHSHIMA et al, 1994OHSHIMA et al, , 1995OHSHIMA et al, , 1996OHSHIMA et al, , 1997YOSHIBA et al, 1996). The class II MHC antigenexpressing cells are thought to serve as the antigenpresenting cells that play an essential role in the initiation of immune responses (STEINMAN, 1991).…”
mentioning
confidence: 99%
“…[1,2]. Indeed, a population of putative post-natal stem cells within the dental pulp stromal cells (DPSCs) was found to have the capability to regenerate a dentin-pulp-like complex, which is composed of mineralized matrix with tubules lined with odontoblasts, and fibrous tissue containing blood vessels in an arrangement similar to the dentin-pulp complex found in normal human teeth [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Odontoblasts are known to express specific proteins such as dentin sialoprotein (DSP), Osteopontin (OPN), Osteocalcin (OCN), type 1-collagen, Alkaline Phosphatase (ALP) and Dentin Matrix Protein-1 (DMP-1). [1,2]. OPN which is an early stage osteoblastic marker is also expressed by odontoblasts since this is a component of their matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Recent Immunohistochemical studies have revealed various types of immunocompetent cells, especially class II MHC antigen-expressing cells, in the normal pulp (JONTELL et al, 1987(JONTELL et al, , 1988OKIJI et al, 1992). The class II MHC antigen-expressing cells are thought to act as antigen-presenting cells that are essential for the initiation of immune responses (JONTELL and BERGENHOLTZ, 1992).…”
mentioning
confidence: 99%